Mini Economica Media Komunikasi Ilmu Ekonomi : The Effect of Preserving Wealth Toward Development in The Light of Maqasid Al-Shariah - Mikail, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
Maqasid al-Shariah becomes important subject in Islamic economic literature due to its role as normative goal in Islamic economic. However , most of literatures regarding Maqasid al-Shariah and economic development are quite qualitative in its approach. Most of articles try to relate consept of Maqasid al-Shariah and describe what must be settled to acquire the objective of Shariah without looking at the interaction among each variable. Therefore, this paper tries to fill this gap by elaborates the concept of safeguarding wealth as one of five values of Maqasid al-Shariah and its role toward economic development, this paper test several variables which represent preserving of wealth towards economic development indicator.